2018
DOI: 10.7717/peerj.5580
|View full text |Cite
|
Sign up to set email alerts
|

Cell-wall-degrading enzymes produced in vitro and in vivo byRhizoctonia solani, the causative fungus of peanut sheath blight

Abstract: Rhizoctonia solani causes the disease peanut sheath blight, involving symptoms of maceration and necrosis of infected tissue, mainly caused by cell-wall-degrading enzymes (CWDEs). This study investigated the production of CWDEs including polygalacturonase (PG), polymethyl-galacturonase (PMG), cellulase (Cx) and β-glucosidase by R. solani in vitro (in liquid culture) and in vivo (in peanut plants). Significant PG, PMG, Cx and β-glucosidase activities were detected in infected tissues including stalk and leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…CAZymes mediate the degradation of cellulose, hemicellulose and pectin in host cell walls and break down the physical barrier of plant immune system, and thus enhancing pathogen virulence (Zheng et al 2013 ; Xia et al 2017 ). CWDEs in R. solani are categorized into seven major families including PG, endo-β- 1,4-glucanase, polymethylgalacturonase, pectin methylesterase, filter paper enzyme, polymethylgalacturonase trans-eliminas and pectin methyltrans-eliminase (Silva et al 2018 ; Xue et al 2018 ; Rathinam et al 2020 ). As a group of hydrolytic enzymes, PGs act on polygalacturonic acid, a key component of plant cell wall, by cleaving the α-(1,4)-glycosidic bonds, and thus causing hydrolysis of pectate.…”
Section: Pathogenicity Factors In R Solanimentioning
confidence: 99%
“…CAZymes mediate the degradation of cellulose, hemicellulose and pectin in host cell walls and break down the physical barrier of plant immune system, and thus enhancing pathogen virulence (Zheng et al 2013 ; Xia et al 2017 ). CWDEs in R. solani are categorized into seven major families including PG, endo-β- 1,4-glucanase, polymethylgalacturonase, pectin methylesterase, filter paper enzyme, polymethylgalacturonase trans-eliminas and pectin methyltrans-eliminase (Silva et al 2018 ; Xue et al 2018 ; Rathinam et al 2020 ). As a group of hydrolytic enzymes, PGs act on polygalacturonic acid, a key component of plant cell wall, by cleaving the α-(1,4)-glycosidic bonds, and thus causing hydrolysis of pectate.…”
Section: Pathogenicity Factors In R Solanimentioning
confidence: 99%
“…The effect of pathogens on the seedlings may be due to its ability to produce a group of enzymes that cause the fall of these seedlings. For example, R. solani produces polygalactoronase (PG), polymethyl-galactoronase (PMG), B-glucosidase and cellulas (Xue et al 2018),…”
Section: Discussionmentioning
confidence: 99%
“…This present study showed the complex mycoparasitism process of T. virens against R. solani. R solani has a unique character because besides having cell wall which contains chitin, it also produces cell wall-degrading enzymes including polygalacturonase (Cattelan, Hartel, & Fuhrmann, 1999), polymethyl-galacturonase (PMG), cellulase (Cx) and β-glucosidase which are potential to inhibit the growth of its antagonist such as Trichoderma (Xue, Zhou, Li, Xiao, & Fu, 2018). On the other hand, T. virens was one of the potential Trichoderma species which is very efficient in degrading cell walls of cellulases (Strakowska, Błaszczyk, & Chełkowski, 2014).…”
Section: Tv1mentioning
confidence: 99%